Distributed Generation Inverter as APF in Dual APF DG interfacing Scheme - Yadiki Rajendra Babu; C. Srinivasa Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Power quality issues are the most concerned area for electrical engineers in these modern days due to indusrtrialization and advancements in electronics. Harmonics are one of the power quality issues that deteriorated the quality of source components delivered to load. Active power filters (APF) are the compensating devices used to mitigate harmonics. Distributed generation (DG) became a trendline due to economical, technical and environmental reasons. This paper presents the harmonic compensation using dual APF sharing compensating signals while active power is fed from distributed generation to grid. DG inverter acts as an interface between DG system and grid to feed active power from DG to grid. In this context, the DG inverter acts both as inverter and APF, used as inverter to invert supply from DG and feeds grid for specified time and also as APF for harmonic compensation thereafter along with dual APF. The proposed system is developed and results are obtained using MATLAB/SIMULINK software. Results are shown for DG inverter feeding active power to grid and also acting as APF. Dual APF characteristics are also shown.